Effector Th1 cells under PD‐1 and CTLA‐4 checkpoint blockade abrogate the upregulation of multiple inhibitory receptors and by‐pass exhaustion. Issue 4 (25th August 2022) - Horzum, Utku; Yanik, Hamdullah; Taskiran, Ekim Z.; Esendagli, Gunes
Abstract: Immune checkpoint inhibitor (ICI) immunotherapy relies on the restoration of T‐cell functions. The ICI receptors are not only found on exhausted T cells but also upregulated upon activation and reach high levels on effector T cells. In an ex vivo model, this study explored the consequences of PD‐1 and cytotoxic T‐lymphocyte antigen (CTLA‐4) blockade applied during specific time frames of T‐cell stimulation that coincide with distinct functional phases in type 1 helper T (Th1) cells. When applied at an early stimulation stage, the checkpoint blockade interfered with the upregulation of multiple inhibitory receptors such as PD‐1, LAG3, TIM‐3 and CTLA‐4. Moreover, extension of the blockade period restricted the hyporesponsiveness in T cells. Alternatively, a short‐term ICI treatment was advantageous when applied at late time frames of Th1 cell stimulation. Here, a transition phase from effector to exhausted state, which coincided with the late time frames of Th1 stimulation, was clearly determined together with the transcriptomics data demonstrating the initiation of significant alterations in metabolic pathways, genetic information processes, effector and exhaustion specific pathways. Applied in this transition phase, PD‐1 and/or CTLA‐4 blockade downregulated the inhibitory receptors which were already present on the effector Th1 cells, potentially through endocytic pathways. Therefore, the efficacy of ICI therapy was modulated by the functional status of T cells and can be improved by modifying the timing and duration of PD‐1 and CTLA‐4 blockade. In conclusion, the ICI therapy not only supports the reactivation of T cells but can also constrain de novo exhaustion. Abstract : Our ex vivo model explored the consequences of PD‐1 and CTLA‐4 blockade applied during specific time frames of T‐cell stimulation that coincide with distinct functional phases in Type 1 helper T (Th1) cells. Prolonged targeting of PD‐1 and CTLA‐4 receptors on the effector Th1 cells can diminish the acquisition of a hyporesponsive state. Alternatively, a short‐term immune checkpoint inhibitor immunotherapy was found to be efficient for the by‐pass of exhaustion and restoration of effector functions on Th1 cells.